Analysis of the Influence of Trust and Financial Literacy on Generation Z’s Interest in Investing in Digital Cryptocurrency Assets - Dachi, Grace Princess; Pangaribuan, Yoshepine (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The advancement of the digital era has driven the emergence of various innovations in the world of investment, one of which is cryptocurrency. This digital asset is increasingly favored by younger generations, particularly Generation Z, due to its ease of access and high-profit potential. However, investment interest is influenced not only by technology and trends but also by psychological factors and individual knowledge, such as financial literacy and trust. This study aims to analyze the influence of financial literacy and trust on Generation Z's interest in investing in cryptocurrency assets in Medan City. The research employed a quantitative method with an associative approach through the distribution of questionnaires to 100 purposively selected respondents. The results of multiple linear regression analysis indicate that, simultaneously, trust and financial literacy have a significant effect on investment interest, with financial literacy also showing a significant partial influence. The coefficient of determination reveals that these two variables contribute 50.1% to the investment interest of Generation Z in cryptocurrency. These findings highlight the importance of improving financial literacy and building public trust to promote the sustainable adoption of digital assets among the younger generation.